2022
DOI: 10.1021/acs.energyfuels.2c00347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on the Spontaneous Adsorption of Aromatic Carboxylic Acids to Methane Hydrate Surfaces: Implications for Hydrate Antiagglomeration

Abstract: Spontaneous adsorption of aromatic carboxylic acids (phenylacetic acid, 2-napthylacetic acid, and 1-pyreneacetic acid) to the CH4 hydrate surface in both liquid hydrocarbon and aqueous phases has been investigated using molecular dynamics simulations, aiming to provide implications for hydrate antiagglomeration. Simulation results indicate that the liquid-phase environment, that is, the liquid hydrocarbon phase or aqueous phase, especially its hydrophilic/hydrophobic property, could profoundly affect the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…CH 4 hydrate formation in the porous clay minerals in the seafloor is affected by many factors, such as the pH and salinity of pore water, surface charge, and organic matters, which can impact the nucleation time and formation kinetics. Experimental studies revealed that the formation conditions of CH 4 hydrates in clay minerals are milder than those in pure water, indicating that clay minerals can promote hydrate formation. Cha and co-workers found that the promoting effect of clay minerals may be because the surfaces of solid particles can serve as nucleation sites . Other experimental studies also found that the confined environments and surface properties of clay minerals could significantly influence the formation conditions and stability of gas hydrates. Molecular dynamics (MD) simulation has been frequently applied to investigate the microscopic behavior of gas hydrates in bulk and in nanopores. The MD study of Yan et al reported that a higher gas–water ratio and larger nanopore size can promote the diffusion of CH 4 molecules and shorten the nucleation time of gas hydrates. , By using MD simulation, Li and co-workers revealed the significant effects of surface properties, solution cations, and surface charges of clay minerals on CH 4 hydrate formation. Recent experimental and MD studies indicated that gas hydrate formation in nano-confined environments is much more complex than that in the bulk phase. On the other hand, salt ions in seawater can adsorb to clay surfaces and affect their physical and chemical properties . Cations and anions are reported to selectively adsorb to different basal surfaces of clay minerals .…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 hydrate formation in the porous clay minerals in the seafloor is affected by many factors, such as the pH and salinity of pore water, surface charge, and organic matters, which can impact the nucleation time and formation kinetics. Experimental studies revealed that the formation conditions of CH 4 hydrates in clay minerals are milder than those in pure water, indicating that clay minerals can promote hydrate formation. Cha and co-workers found that the promoting effect of clay minerals may be because the surfaces of solid particles can serve as nucleation sites . Other experimental studies also found that the confined environments and surface properties of clay minerals could significantly influence the formation conditions and stability of gas hydrates. Molecular dynamics (MD) simulation has been frequently applied to investigate the microscopic behavior of gas hydrates in bulk and in nanopores. The MD study of Yan et al reported that a higher gas–water ratio and larger nanopore size can promote the diffusion of CH 4 molecules and shorten the nucleation time of gas hydrates. , By using MD simulation, Li and co-workers revealed the significant effects of surface properties, solution cations, and surface charges of clay minerals on CH 4 hydrate formation. Recent experimental and MD studies indicated that gas hydrate formation in nano-confined environments is much more complex than that in the bulk phase. On the other hand, salt ions in seawater can adsorb to clay surfaces and affect their physical and chemical properties . Cations and anions are reported to selectively adsorb to different basal surfaces of clay minerals .…”
Section: Introductionmentioning
confidence: 99%
“…Acids and Hydrates. Several authors 31,43,196,197,207,208 report the importance of crude oil acids on hydrate antiagglomeration. Some of them state that acids change hydrate wettability from water-wet to oil-wet and consequently reduce hydrate agglomeration and plugging.…”
Section: Natural Hydrate Antiagglomeration In Crude Oil Systems: Role...mentioning
confidence: 99%
“…24 Several MD simulation studies explored the nucleation and growth of CH 4 hydrate in the slit-nanopores of silica or clay to reveal the effects of geological factors on hydrate formation in marine sediments, including sediment solid surfaces, seawater ions, and organic matter. [25][26][27][28] Recent experimental studies inferred that the crystal structure and stability of CH 4 hydrate conned in sediments might be mainly affected by the hydrophilic/hydrophobic properties of sediment surfaces. 29 Despite many achievements, the microscopic mechanism of hydrate formation in porous materials is still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%